Perceived impact on efficiency and safety of experienced American physician assistants/associates in acute hospital care in England: findings from a multi-site case organisational study. Issue 10 (November 2020) - Drennan, Vari M; Calestani, Melania; Taylor, Francesca; Halter, Mary; Levenson, Ros
Summary: Objectives: To investigate the contribution, efficiency and safety of experienced physician associates included in the staffing of medical/surgical teams in acute hospitals in England, including facilitating and hindering factors. Design: Mixed methods longitudinal, multi-site evaluation of a two-year programme employing 27 American physician associates: interviews and documentary analysis. Setting: Eight acute hospitals, England. Participants: 36 medical directors, consultants, junior doctors, nurses and manager, 198 documents. Results: Over time, the experienced physician associates became viewed as a positive asset to medical and surgical teams, even in services where high levels of scepticism were initially expressed. Their positive contribution was described as bringing continuity to the medical/surgical team which benefited patients, consultants, doctors-in-training, nurses and the overall efficiency of the service. This is the first report of the positive impact that, including physician associates in medical/surgical teams, had on achieving safe working hours for doctors in training. Many reported the lack of physician associates regulation with attendant legislated authority to prescribe medicines and order ionising radiation was a hindrance in their deployment and employment. However, by the end of the programme, seven hospitals had published plans to increase the numbers of physician associates employed and host clinical placements for student physician associates. Conclusions: The programme demonstrated the types of contributions the experienced physician associates made to patient experience, junior doctor experience and acute care services with medical workforce shortages. The General Medical Council will regulate the profession in the future. Robust quantitative research is now required.